Protective effect of green tea on dentin erosion and abrasion - Melissa Thiemi Kato; Ana Carolina Magalhães; Daniela Rios; Angélica Reis Hannas; Thomas Attin; Marília Afonso Rabelo Buzalaf (University of São Paulo, 2009)
OBJECTIVE: This in situ study evaluated the protective effect of green tea on dentin erosion (ERO) and erosion-abrasion (ABR). MATERIAL AND METHODS: Ten volunteers wore intraoral palatal appliances with bovine dentin specimens subjected to ERO or ERO + toothbrushing abrasion performed immediately (ERO+I-ABR) or 30 min after erosion (ERO+30-min-ABR). During 2 experimental 5-day crossover phases, the volunteers rinsed with green tea or water (control, 1 min) between each erosive (5 min, cola drink) and abrasive challenge (30 s, toothbrushing), 4x/day. Dentin wear was measured by profilometry. RESULTS: The green tea reduced the dentin wear significantly for all conditions compared to control. ERO+I-ABR led to significantly higher wear than ERO, but it was not significantly different from ERO+30-min-ABR. ERO+30-min-ABR provoked significant higher wear than ERO, only for the placebo treatment. CONCLUSIONS: From the results of the present study, it may be concluded that green tea reduces the dentin wear under erosive/abrasive conditions.